1980
DOI: 10.1149/1.2129863
|View full text |Cite
|
Sign up to set email alerts
|

The Electrosorption of Methane and Its Potentiodynamic Electrooxidation on Platinized Platinum

Abstract: The electrosorption of methane on platinized platinum and the potentiodynamic oxidation of the electrosorbed species in 1N H2SO4 solution is studied at 60°C. Two electrosorbed species are distinguished through the I/E characteristics recorded under different perturbation conditions. These species are assigned to COH‐type and CO‐type adsorbed species. The latter can be transformed into the former by electrochemical reduction in the potential range of the hydrogen adatoms. The number of the electrocatalyst s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 20 publications
2
27
1
Order By: Relevance
“…Case 1. Sustersic et al [53] showed that methane adsorption on platinum surface started from a potential 0.2 V versus NHE and reached a maximum adsorption peak at 0.25 V (versus NHE). In HT-PEMFC the anode potential does not exceed 50 mV (even at high current densities of 1.5 A cm −2 ) which is far below the minimum potential suggested for methane adsorption.…”
Section: Phosphoric Acid Concentration Temperature and Watermentioning
confidence: 99%
“…Case 1. Sustersic et al [53] showed that methane adsorption on platinum surface started from a potential 0.2 V versus NHE and reached a maximum adsorption peak at 0.25 V (versus NHE). In HT-PEMFC the anode potential does not exceed 50 mV (even at high current densities of 1.5 A cm −2 ) which is far below the minimum potential suggested for methane adsorption.…”
Section: Phosphoric Acid Concentration Temperature and Watermentioning
confidence: 99%
“…Bagotzky et al [13] proposed a mechanism in which a chemisorbed hydrocarbon reacts in combinations of (a) dehydrogenation reactions and (b) reactions with adsorbed hydroxyl groups. Electroadsorption studies of methane have been explained using the Bagotzky mechanism [14]. In situ infrared spectroscopy experiments [15] on electrodes immersed in HClO 4 electrolyte, identified the following species, H AC* @O, HO AC* @O, and @C @O.…”
Section: Several Other Factors Influence the Performance Ofmentioning
confidence: 99%
“…Useful guidance for the understanding potentio‐dynamic mechanism is to combine the mechanistic data from standard measurements, and in‐situ analysis. Earlier, *CHO, *COOH, and *CO species were suggested to be involved in methane oxidation based on potentio‐dynamic measurements [52–53] . Emerging in‐situ spectroscopic techniques could confirm such considerations.…”
Section: Methane Electro‐engineeringmentioning
confidence: 98%